Kurikulum Madrasah sebagai Penyeimbang Dampak Negatif Perkembangan Teknologi Digital - Nugraha, Mulyawan Safwandy; Saputra, Wahyu Andi (Lembaga Yasin AlSys, 2024)
The development of digital technology has a significant impact on various sectors of life, including education. This paper explores the role of the madrasah curriculum as a counterbalance to the negative effects of digital technology development. Through an analysis of the madrasah context, including characteristics of the madrasah, students, educators, facilities, partnerships, potential funding sources, and socio-cultural environment, it was found that the madrasah curriculum needs to identify and explore differentiating strengths according to its characteristics. The learning plan for madrasahs includes the formulation of Learning Outcomes, learning objectives, assessments, and learning resources involving both extracurricular activities and projects that strengthen student profiles. Additionally, planning priority programs for madrasahs is an important focus. In the classroom, the learning plan includes the preparation of teaching modules, teaching materials, and other documentation reflecting the core learning objectives. The madrasah curriculum plays a central role as a counterbalance by integrating religious values, wise digital literacy, and moral development. With this approach, the madrasah curriculum shapes comprehensive Islamic individuals who are able to face modern technological challenges while remaining steadfast in traditional values. Thus, the madrasah curriculum becomes an essential instrument in shaping a balanced and adaptive generation in this digital era.